1995
DOI: 10.2527/1995.7392524x
|View full text |Cite
|
Sign up to set email alerts
|

Body composition of gilts at puberty.

Abstract: The relationship between body composition and the occurrence of puberty was evaluated using 93 Yorkshire x Landrace gilts. At approximately 60 d of age gilts were purchased and placed in a heated confinement unit where they were housed for the duration of the study. Ad libitum access to feed was provided throughout the study. Gilts were moved, mixed, and initially exposed to mature boars at approximately 120 d of age to encourage the earliest possible occurrence of puberty. Empty body weights of water, fat, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
39
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 7 publications
7
39
0
1
Order By: Relevance
“…AA gilts had lower meat percentage and muscle thickness, higher fat thickness and lower ham width compared with GG gilts (Van den Broeke et al, 2015). Our results are therefore in accordance with the results of Rozeboom et al (1995) and Patterson et al (2002), that is that no association can be found between body conformation and the attainment of puberty in gilts.…”
supporting
confidence: 89%
“…AA gilts had lower meat percentage and muscle thickness, higher fat thickness and lower ham width compared with GG gilts (Van den Broeke et al, 2015). Our results are therefore in accordance with the results of Rozeboom et al (1995) and Patterson et al (2002), that is that no association can be found between body conformation and the attainment of puberty in gilts.…”
supporting
confidence: 89%
“…Thus, it appears that developing gilts with restricted energy intake reduces age at puberty. However, natural variation in gilt prepubertal ADG within a population does not appear to be related to age at puberty (Rozeboom et al, 1995).…”
Section: Discussionmentioning
confidence: 87%
“…In reviewing growth and puberty reports, Rauw et al (1998) noted that gilts with a greater lean percentage had a delayed onset of puberty, and negative genetic correlations have been reported between growth rate and estrus signs at puberty (Rydhmer et al, 1994). Leptin has long been recognized as a putative signal that links metabolic status with the neuroendocrine control of reproduction and puberty in pigs, and attainment of puberty may be related to a metabolic state at a critical period of development rather than a level of body composition (Rozeboom et al, 1995).…”
Section: Discussionmentioning
confidence: 99%